Respuesta :
x1 = -2, y1 = -3
x2 = 2, y2 = 3
Insert values into slope formula:
m = (3)-(-3)/2-(-2)
m = 6/4
m = 3/2
y-intercept: b = y1 - m * x1
b = -3 - (3/2) * (-2)
b = 0
y = mx + b
y = 3/2x
equation of line:
3x - 2y = 0
x2 = 2, y2 = 3
Insert values into slope formula:
m = (3)-(-3)/2-(-2)
m = 6/4
m = 3/2
y-intercept: b = y1 - m * x1
b = -3 - (3/2) * (-2)
b = 0
y = mx + b
y = 3/2x
equation of line:
3x - 2y = 0
Answer:
y = 3/2x
Step-by-step explanation:
[tex] \frac{ 3 + 3}{2 + 2} = \frac{6}{4} = \frac{3}{2} [/tex]
[tex] - 3 = ( \frac{3}{2} ) - 2 + y \\ - 3 = - 3 + y \\ 0 = y[/tex]